Elliptic and triangular flow of (anti)deuterons in Pb-Pb collisions at √ˢɴɴ =5.02 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akbar, Z.; et al. (American Physical Society, 2020)
The measurements of the (anti)deuteron elliptic flow (v₂) and the first measurements of triangular flow (v₃) in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon collision √ˢɴɴ = 5.02 TeV are presented. A mass ordering at low transverse momentum (Pᴛ) is observed when comparing these measurements with those of other identified hadrons, as expected from relativistic hydrodynamics. The measured (anti)deuteron v₂ lies between the predictions from the simple coalescence and blast-wave models, which provide a good description of the data only for more peripheral and for more central collisions, respectively. Themass number scaling, which is violated for v₂, is approximately valid for the (anti)deuterons v₃. The measured v₂ and v₃ are also compared with the predictions from a coalescence approach with phase-space distributions of nucleons generated by IEBEVISHNU with AMPT initial conditions coupled with URQMD, and from a dynamical model based on relativistic hydrodynamics coupled to the hadronic afterburner SMASH. The model predictions are consistent with the data within the uncertainties in midcentral collisions, while a deviation is observed in the most central collisions.
Keywords: Physics; Hadron; Nucleon; Nuclear physics; Elliptic flow; Coalescence (physics); Deuterium; Impact parameter; Particle physics; Quantum mechanics; Heavy ion; https://purl.org/pe-repo/ocde/ford#1.03.04